Insights into the Quark-Gluon Vertex from Lattice QCD and Meson Spectroscopy - Rojas, E.; El-Bennich, B. [UNESP]; Melo, J. P. B. C. de; Paracha, M. Ali (Springer, 2015)
By comparing successful quark-gluon vertex interaction models with the corresponding interaction extracted from lattice-QCD data on the quark's propagator, we identify common qualitative features which could be important to tune future interaction models beyond the rainbow ladder approximation. Clearly, a quantitative comparison is conceptually not simple, but qualitatively the results suggest that a realistic interaction should be relatively broad with a strong support at about 0.4-0.6 GeV and infrared-finite.